Synthesis Process of Amphoteric Polyacrylamide - Zhang, Linlin; Nie, Rongchun; Ma, Shuai; Wang, Yanfen (Asian Journal of Chemistry, 2015)
In this work, amphoteric polyacrylamide(AmPAM) was synthesized via copolymerization and homopolymerization cohydrolysis based on photoinitiator as initiator, respectively. The result indicates that monomer ratio, monomer concentration, the amount of the initiator and pH have effects on the intrinsic viscosity of polymer. It achieved the best inherent viscosity when monomer ratio of n(AM):n(NaAA): n(DMC) was 1: 0.65:0.16, the monomer concentration was 35 %, the amount of the initiator was 0.08 % and pH value was adjusted to 7 by using copolymerization. The best intrinsic viscosity of the product was 759 mL/g and acrylamide (AM) conversion rate was 99.97 %. In contrast, it achieved the best inherent viscosity when monomer ratio of n(AM): n(NaOH): n(DMC) was 1: 0.15: 0.18, the monomer concentration was 35 %, the amount of the initiator was 0.06 % and pH value was adjusted to 7 by using homopolymerization cohydrolysis. The result demonstrates that the best intrinsic viscosity of the product was 531 mL/g and acrylamide conversion rate was 99.94 %.